HUBUNGAN PELAKSANAAN SENAM HAMIL PADA IBU HAMIL 36 MINGGU DENGAN LAMA PROSES PERSALINAN KALA I DAN KALA II DI BPS â€œBâ€ BUKITTINGGI TAHUN 2014 - Syelvi, Syelvi; Mutia Felina, Mutia Felina (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
Maternal Mortality occurred due to complications of pregnancy and childbirth, caused by prolonged labor. Efforts to reduce the incidence of prolonged labor, namely the implementation of pregnancy exercise in pregnancy may help reduce the incidence of length delivery, lowering maternal anxiety in the face of strengthening the role of labor contractions, maintain flexibility of the muscles of the abdominal wall, the pelvic floor muscles and hold additional pressure related with childbirth.The arms of this study is to determine the "Implementation of the relationship with the Old Labor Gymnastics Pregnant Term I and Term II in the Mother Maternity in Midwife House Practicy" B " Bukit Ambacang Bukittinggi Year 2014." The research method used Analytical Survey observational approach Cross Sectional Study, sampling is conducted by Accidental Sampling. Data retrieved through direct observation and interviews at the time of the study respondents encountered, then the data is processed with computerized using chi-square formula and alpha value of 0.05 (95%). The result showed that 58.8% do gymnastics pregnant and 61.8% of respondents are of normal birth with the first stage, as well as 67.6% of respondents normal delivery with the second stage. From the results, 61.8% of respondents who labor with the first stage of normal and 58.8% of respondents of which do pregnancy exercise during the pregnancy. And 67.6% of respondents to the second stage of normal childbirth and 58.8% of the respondents including doing gymnastics pregnant. Conclusions The results of this study are more disciplined pregnant woman doing pregnancy exercise, the more smoothly the process of birth mothers. Then there is a significant correlation between the implementation of the long pregnancy exercise first stage of labor and in the second stage of the Midwife House Practicy "B" Bukit Ambacang Bukittinggi Year 2015. Women who carry pregnancy exercise routine during the pregnancy can reduce the occurrence of Term I and Term II. Research expect in the future pregnancy exercise program is more on the increase again so that expectant mothers willing to carry out the pregnancy exercise so as to reduce complications and complications in the first stage of labor,especiallylabor and second stage.